Malaysia's response to Rohingya refugee crisis, 2015-2017: an analysis - Nur Syazwani Muzafarkamal (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This dissertation investigated and analyzed Malaysia's response to the Rohingya crisis during 2015-2017. This study was undertaken because of its relevance to the management of the Rohingya refugees in Malaysia. A series of violent attacks on the Rohingya community in Rakhine, Myanmar, from 2015 to 2017 received worldwide attention including Malaysia. As a result of these attacks, Rohingyas fled to countries such as Bangladesh and Malaysia. The main objective of this research was to assess Malaysia's response in dealing with the increasing number of Rohingya refugees in Malaysia through the principle of the concept of Responsibility to Protect (R2P). The research also examined the applicability of the principle of 'humanitarian assistance' by the United Nations (UN) to protect the Rohingyas. In order to achieve the objectives of this research, the study examined the roles of various international actors such as the Association of Southeast Asian Nations (ASEAN), the Organization of Islamic Cooperation (OIC), the UN, as well as the European Union (EU) in handling the Rohingya refugee crisis. This dissertation also examined Malaysia's policy of assisting Bangladesh to deal with the massive influx of Rohingya refugees in Bangladesh. The dissertation adopted a qualitative research methodology. Many NGOs in Malaysia were interviewed to get their insight into this matter. As part of the research, representatives of a number of non-governmental organizations (NGOs) in Malaysia which included Majlis Perundingan Pertubuhan Islam Malaysia (MAPIM), Yayasan Amal Malaysia, MyCare Malaysia, Centre for Human Rights Research and Advocacy (CENTHRA), and Malaysia Relief Agency were interviewed. Officials from Wisma Putra (Ministry of Foreign Affairs, Malaysia) were also interviewed. In order to gauge the response of Bangladesh to the Rohingya refugee crisis, the Political Secretary of Bangladesh High Commission in Kuala Lumpur was consulted. The analysis in this dissertation found that despite having a dilemma that whether or not to be the signatory country to the 1951 Refugee Convention, there were, in fact, many ways to ensure Malaysia could handle the issue of this crisis. Malaysia was very critical of Myanmar for its military crackdown on Rohingyas. But it was also handicapped by its own policy of treating all refugees in Malaysia as illegal immigrants. Although Rohingya refugees living in Malaysia faced many social and economic problems, Malaysians, in general were very sympathetic to the cause of the Rohingyas.